FACT SHEET; LABOR-MANAGEMENT HEALTH FUNDS: PAYING THE MEDICAL BILLS OF 30 MILLION AMERICANS (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Coalition for Worker's Health Care Funds fact sheet on labor-management health funds. Describes purpose and functions of such health funds. Lists states in which worker's health funds have filed lawsuits against tobacco companies because of tobacco related disease costs.